2017
DOI: 10.3390/f8090324
|View full text |Cite
|
Sign up to set email alerts
|

Functional Response Trait Analysis Improves Climate Sensitivity Estimation in Beech Forests at a Trailing Edge

Abstract: Functional response traits influence the ability of species to colonize and thrive in a habitat and to persist under environmental challenges. Functional traits can be used to evaluate environment-related processes and phenomena. They also help to interpret distribution patterns, especially under limiting ecological conditions. In this study, we investigate landscape-scale functional distribution responses of beech forests in a climatic transitional zone in Europe. We construct empirical density distribution r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Other studies on species richness along elevational gradients in Mexico have reported a decreasing pattern of vascular plants (Vázquez-García & Givnish 1998, Salas-Morales & Meave 2012) or a hump-shaped pattern (Sánchez-González & López-Mata, 2005). Some of the discrepancies in assessing spatial richness patterns between different studies could be sampling effort (i.e., plot size and number), selection of growth forms (i.e., trees, shrubs, herbs and epiphytes) and partial or total analysis across the elevational gradient (Lomolino 2001, Nogués-Bravo et al 2008, McCain & Grytnes 2010.…”
Section: Group Of Variablesmentioning
confidence: 89%
“…Other studies on species richness along elevational gradients in Mexico have reported a decreasing pattern of vascular plants (Vázquez-García & Givnish 1998, Salas-Morales & Meave 2012) or a hump-shaped pattern (Sánchez-González & López-Mata, 2005). Some of the discrepancies in assessing spatial richness patterns between different studies could be sampling effort (i.e., plot size and number), selection of growth forms (i.e., trees, shrubs, herbs and epiphytes) and partial or total analysis across the elevational gradient (Lomolino 2001, Nogués-Bravo et al 2008, McCain & Grytnes 2010.…”
Section: Group Of Variablesmentioning
confidence: 89%
“…Oak species in dry areas with the lowest aridity value (AI = 0.78) in lowlands possess high wood densities and lower relative hydraulic conductivity, and in higher altitudes with higher aridity values (AI = 1.78) humid places possess taller oaks with higher relative hydraulic conductivity and lower wood density. Seasonal patterns in temperature and precipitation influence ecological process as seedling growth, productivity and phenology among others, all of which have an impact on the survival and establishment of plants in mountainous areas ( Tang and Fang 2006 ; Salamon-Albert et al 2017 ). Seasonal precipitation regimen is extremely relevant such as precipitation of warmest quarter because it determines the highest level of drought stress, and plants must avoid or tolerate the drought.…”
Section: Discussionmentioning
confidence: 99%
“…In Romania, climate change did not affect these forests, although the increment was reduced in June and September and the amount of precipitation decreased in summer months [35]. The differences in the temperatures between the hottest and the coldest months and between the mean annual precipitation rates were proven to be the most important parameters of the resistance and adaptability of beech forests [47]. The same study noted that precipitation in the winter period will be an important factor of ecological resistance and adaptability of this species to climate change.…”
Section: Introductionmentioning
confidence: 96%